Pengembangan Model Pembelajaran Inkuiri Berbasis Pendidikan Karakter Dalam Membentuk Karakter Siswa Pada Mata Pelajaran Pendidikan Agama Kristen di SMAN 14 Bandar Lampung - S Supriyono; R Riswandi; Dwi Yulianti (WACANA AKADEMIKA: Majalah Ilmiah Kependidikan, 2022)
This study aims to develop an inquiry learning model design based on character education in shaping the character of students in Christian education subjects at SMAN 14 Bandar Lampung and to review the effectiveness and efficiency of the learning process using the developed learning design products. This type of research is research and development (R&D) using the development of the dick & carey model. The instruments in this study were expert validation sheets, teacher and student responses questionnaire sheets, and learning implementation observation sheets. The data analysis techniques used in this research are descriptive analysis, expert validation data analysis, and test data analysis. The results of the research based on the data and discussion concluded that the product of the inquiry learning model based on character education to shape the character of students in PAK subjects was declared valid, attractive, efficient and effective based on the assessments of experts, teachers and students. Suggestions given at least for readers can develop into other aspects of the character or other subjects